2010
DOI: 10.1051/agro/2009042
|View full text |Cite
|
Sign up to set email alerts
|

Basis for designing a tool to evaluate new cultivars

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…Once stabilized, the genotype is tested through formal regulatory procedures that have to be officially registered. As the stage of official registration is mandatory to access the market, its criteria strongly orient the design of varieties Lecomte et al (2010). At EU level, intellectual property of the varieties ensures recognition of the private breeding companies' ownership of the varieties they designed, but these varieties can nevertheless be used and cross-bred by anyone else to design other varieties Make the registration criteria and procedure evolve within the existing strong legal framework that attributes most value to the productivity of the variety in order to meet agro-ecological requirements…”
Section: Plant Varietymentioning
confidence: 99%
See 2 more Smart Citations
“…Once stabilized, the genotype is tested through formal regulatory procedures that have to be officially registered. As the stage of official registration is mandatory to access the market, its criteria strongly orient the design of varieties Lecomte et al (2010). At EU level, intellectual property of the varieties ensures recognition of the private breeding companies' ownership of the varieties they designed, but these varieties can nevertheless be used and cross-bred by anyone else to design other varieties Make the registration criteria and procedure evolve within the existing strong legal framework that attributes most value to the productivity of the variety in order to meet agro-ecological requirements…”
Section: Plant Varietymentioning
confidence: 99%
“…It is also based on the use of specific methods to assess the objects under design. For example, breeders use multi-environment trials, carried out on several locations and for several years, to compare their new varieties with current varieties (Lecomte et al 2010): Only the new varieties that perform well under a wide range of conditions are kept. This type of procedure, which also exists for plant protection products, aims at designing objects with a broad spectrum of use.…”
Section: Design In Agriculture Requires Renewing the Way To Address Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative traits are vulnerable to environmental forces responsible for the genotype-tophenotype gap. For instance, in multi-environmental trials of wheat, pea, soybean and maize, the environment effect has been shown to be preponderant, representing some 50-80% of total variation, whilst variation due to the genotype effect was only 10-25% (Lecomte et al 2010).…”
Section: The Isolation Environment Optimizes Response To Selectionmentioning
confidence: 99%
“…Phenotypes of the training populations were evaluated in multi-environmental field trials. A crop diagnosis modelling approach (Lecomte et al, 2010) was applied to identify the factors that limit plant productivity under each environment and to calculate the effect of these limiting factors on yield in the different genotypes. Contrary to phenotypic selection, running selection based on genomic-estimated breeding values from single traits allows identifying expected top lines without a priori on a favourable ideotype or plant characteristics other than the target trait.…”
Section: Deducing Targeted Ideotypes From Best Candidates Identifiedmentioning
confidence: 99%